Epidemiological profile of congenital syphilis in the state of Mato Grosso do Sul, Brazil - Santos Júnior, Gilvan Caetano dos; Carvalho, Maressa Maziero de; Salvatori, Alessandra; Barbosa, Karine Ferreira; Arruda, Larissa Domingues Castilho de; Frias, Danila Fernanda Rodrigues (Revista Prevenção de Infecção e Saúde, 2024)
Introduction: When syphilis is not treated during pregnancy, it results in a considerable proportion of early fetal and neonatal deaths, with a high probability of vertical transmission, and when this occurs, Congenital Syphilis (CS) develops. Aim: To evaluate the epidemiological profile of SC in the state of Mato Grosso do Sul, from 2012 to 2021. Design: A cross sectional, descriptive, retrospective, qualitative and quantitative study was carried out, limited to the years 2012 to 2021, with secondary data and the variables: child’s age, final diagnosis, mother’s age range, race, or color, having undergone prenatal care, time of diagnosis of maternal syphilis, maternal treatment regimen and deaths due to CS in children under one year of age. Results: 2,932 cases of CS were reported during the period. In the state, 88.1% of cases were in children less than 7 days old. 71.4% of mothers reported receiving prenatal care. Given the information about the mother’s therapeutic regimen, 39.1% were inadequate, 28.8% did not receive treatment and in only 3.2% the treatment was adequate. Implications: The CS incidence rate in the State remained above the established national parameter, which is why it is necessary to invest more in epidemiological surveillance, as this is the first step to controlling the disease.